Gallstone disease classification using SLOA-optimized CatBoost classifier with explainable AI - Prosenjit Das; Md. Ayaj Uddin Khan; Proshenjit Sarker; Abdullah-Al Nahid (PLoS ONE, 2026)
Gallstones are small stones that form in the gallbladder. Around 80% of individuals with gallstones do not present any symptoms. Despite the high accuracy of image-based machine learning (ML) models in the detection of gallstones, less research has been carried out regarding tabular data. This paper has discussed a publicly available tabular dataset in order to study some predictive models to determine the presence of gallstones. We have employed the Catboost (CB) classifier model and the Sea Lion Optimization Algorithm (SLOA) in our study. In this project, the primary methods that are explored include CatBoost with cross-validation and CB optimized using the SLOA with cross-validation. The CB model techniques using 5-fold cross-validation have attained a mean accuracy of 79.58%, a mean F1-score of 79.01%, a mean precision of 80.91%, and a mean recall of 77.36% using a total of 38 features. In particular, fold-1 has attained an accuracy of 86.46%, F1-score 85.39%, precision of 88.37%, and recall of 82.61% among the 5-fold cross-validation of the CB model. In addition, the SLOA_CB model of 5-fold cross-validation has achieved a mean accuracy of 80.42%, a mean F1-score of 79.94%, a mean precision of 81.97%, and a mean recall of 77.76%, using the 19 selected features. In this case, fold-4 has attained an accuracy of 87.50%, F1-score, precision, and recall of 87.23%, which implies that the classification performance is balanced. Lastly, SHAP, LIME, and DiCE have been applied to the model explainability, and the most influential features in all cases, regarding the prediction of gallstone disease, are C-Reactive Protein (CRP) and Vitamin D.